Design of 6E Instructional Model Integrated Augmented Reality to Improve Thinking Ability of 3D Geometry Viewed from Geometry Self-efficacy of Junior High School Students - Sudirman, - (2022)
The COVID-19 pandemic has encouraged more intensive use of information and communication technology (ICT) in mathematics learning. However, school unpreparedness and teachers' low knowledge and ability to use ICT, which must be integrated with didactic, pedagogical, and material aspects, result in low student achievement in mathematics. Based on initial observations of several junior high schools in Indramayu Regency, it was indicated that during the COVID-19 pandemic, students had difficulty in understanding 3D geometry material, so 3D geometry learning was seen as less effective. This study aims to produce an AR-integrated 6E-IM learning design that can improve 3D geometric thinking skills by paying attention to students' geometry self-efficacy. This research used a mixed-method approach with a sequential exploratory type. The participants in this study were mathematics teachers and junior high school students in one of the N SMPs in the Indramayu Regency. Data collected from the qualitative stage were analyzed using the Miles and Huberman model analysis procedure, while the data obtained from field testing was analyzed quantitatively using parametric statistics, namely Anava and Ancova. The findings of the study reveal that 1) at the initial observation, students have difficulty in representing, identifying spatial structures, and measuring the surface area and volume of 3D geometry; 2) AR technology can be integrated into 3D geometry teaching materials and 6E-IM learning; 3) there is a significant difference in the improvement of KBG3D between students who learn using AR integrated 6E-IM, 6E-IM, and conventional learning; 4) there is a significant effect of learning (6E-IM integrated AR and 6E-IM) on increasing the ability to think 3D geometry by paying attention to students' geometry self-efficacy.